AZ Amerikai Egyesült Államok és Magyarország között 1921-ben megkötött békeszerződés - Vizi, László Tamás (Közép-Európai Közlemények, 2015)
After Germany introduced the unrestricted submarine warfare at the beginning of February 1917, the United States declared war on 6th April 1917 on Berlin and joined the First World War beside the Allied countries. In response to the declaration of war the Austro-Hungarian Monarchy broke off its diplomatic relations with Washington on the 9th April 1917. The martial law between the two states came into force on the 7th December 1917 with the US’s declaration of war. The First World War ended with the victory of the Entente and the peace was dictated by the victors. US President Woodrow Wilson achieved that the victorious powers adopted the League of Nations Covenant in April 1919, which became part of the Paris peace treaties. The US domestic politics was divided over the League of Nations, and as a result of that the US Senate has not ratified neither Germany’s nor Austria’s and Hungary’s peace treaties. The US concluded a separate peace treaty with the losing countries on the basis of the Knox-Porter-resolution. In the history of diplomacy the Knox-Porter-resolution became known as a peace resolution that abolished the state of war between the parties, but the United States has assured all the rights guaranteed by the ceasefire agreement and the peace treaty. The study deals with the preliminaries, the parliamentary debate, details of the ratification, and also describes the most important points of the peace treaty between the United States and Hungary signed on 29th August 1921.